Perception of consumers' awareness about sustainability of fashion brands - Doroteja Mandarić; Anica Hunjet; Goran Kozina (Journal of Risk and Financial Management, 2021)
Consumers' perception, awareness, and behavior toward sustainable fashion were surveyed with a questionnaire in which 263 respondents participated, and obtained data were primarily analyzed using descriptive statistics and t-test. The focus of this research was consumer attitudes toward sustainable business practices of fashion brands. Based on the conducted research, differences were found between sexes in the perception of their own awareness of sustainability in fashion, where women consider their own awareness to be higher than men's. The perception of fashion sustainability awareness in women younger than 35 and those over 36 was also examined. The research showed a gap between consumers' awareness, their positive attitude toward sustainable fashion, and a lack of action in that direction when making purchasing decisions. The results of these studies provide a better understanding of one's own perception of awareness in terms of fashion sustainability and various connected factors, as well as difference in both sexes' awareness of these factors, which may influence consumer behavior related to sustainable fashion products. Thus they can facilitate the implementation of relevant strategies in the fashion industry.
Keywords: 330; sustainable fashion; sustainable business; consumer behavior; consumer information; corporate social responsibility